2017
DOI: 10.3171/2017.7.peds17161
|View full text |Cite
|
Sign up to set email alerts
|

The rare case of a large complex intraosseous cranial arteriovenous malformation with successful multidisciplinary management

Abstract: Intraosseous cranial arteriovenous malformations (AVMs) are very rare, challenging entities. The authors report the case of an extracranial parietooccipital vascular lesion. A 12-year-old boy presented with accelerated growth of a right scalp lesion over a few months. Digital subtraction angiography showed a large, right parietooccipital intraosseous AVM with multiple complex arterial feeders. Treatment of these lesions is difficult and can necessitate a multidisciplinary approach. In the featured case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Interestingly, the endothelial wall of these AVMs also expresses high levels of VEGF compared with normal endothelium, which could lead to the enlargement or regrowth of AVMs. 11,12 Spinal arteriovenous shunts can be either congenital or acquired, with congenital lesions more often manifesting in childhood 13,14 or early adulthood. Traditionally, type I (dural) AVFs are considered to be acquired lesions, whereas types II (glomus), III, and IV (pial) are considered congenital lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the endothelial wall of these AVMs also expresses high levels of VEGF compared with normal endothelium, which could lead to the enlargement or regrowth of AVMs. 11,12 Spinal arteriovenous shunts can be either congenital or acquired, with congenital lesions more often manifesting in childhood 13,14 or early adulthood. Traditionally, type I (dural) AVFs are considered to be acquired lesions, whereas types II (glomus), III, and IV (pial) are considered congenital lesions.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] Surgical excision of intraosseous AVMs offers the highest likelihood of cure; however, surgery can be quite morbid, especially in cases with extensive involvement, and may require future reconstruction of the residual defect. 11,19,32 In cases of small intraosseous AVMs, surgery alone has been successful in achieving complete resolution of symptoms. 19 Molina et al described a case in which a 1 cm intraosseous AVM of the spine was resected en bloc, leading to resolution of the patient's symptoms and improvement of his scoliosis 32 months following the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have concluded that common femoral artery (CFA) access should be standard for pediatric angiographic procedures. 1,9,12 Among the closure devices approved for adult use, pertinent disadvantages may include an incompatible device size relative to the small CFA diameter in children, a mural or transmural attachment with a cicatricial action, and retained intraluminal biomaterial after completion of the procedure. 12 The MynxGrip device (AccessClosure Inc.) achieves hemostasis through the delivery of an extravascular, nonadhesive, expansile, water-soluble foam plug that fully resorbs over 1 month.…”
Section: T Shokuhfar Et Almentioning
confidence: 99%